The use of by-products as soil amendments in the agricultural and forestry sector - Paganini, Enzo Antônio Lecciolle [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Sewage sludge is a solid or semi-solid residue generated during wastewater treatment, rich in macro- and micronutrients, and potentially useful as an agricultural or forestry input. In addition to providing nutrients, it can improve soil physical characteristics, such as aeration and water retention capacity. However, its application should be done with caution, considering the possible presence of potentially toxic elements that can harm plant development. To deepen our understanding of the effects of sewage sludge application on seedling production, this thesis was structured in two phases. The first consisted of a systematic literature review followed by a meta-analysis, based on the PRISMA 2021 protocol, analyzing recent articles with quantitative data on the effects of sewage sludge on soils and plants. The second phase involved two pot experiments conducted for 120 days under greenhouse conditions, with different tree species used in urban landscaping, grown in substrates with varying proportions of domestic sewage sludge. The experiments were conducted to evaluate the effects of sewage sludge on soil chemical parameters, plant growth through non-destructive analyses (monthly stem height and diameter), and nutrient concentrations accumulated in plants through final chemical analyses of tissues separated between shoots and roots. In both experiments, statistical analyses included ANOVA and Tukey's test at a 5% significance level, as well as multivariate analyses (PCA and PFA) to identify the factors that most contributed to the variations between treatments. The first experiment was conducted in Sassari, Sardinia, Italy, using Nerium oleander as the species. The treatments consisted of T0 (100% commercial substrate), T1 (25% centrifuged sewage sludge (SS) + 50% urban soil (US) + 25% perlite), T2 (50% SS + 25% US + 25% perlite) and T3 (75% SS + 25% perlite), each with six replicates (pots). The control treatment (T0) showed the best initial performance in height, stem diameter and aerial biomass, followed by T1, T2 and T3. In the treatments with ≥50% sludge (T2 and T3), leaf chlorosis was observed in the seedlings during the first 60 days, possibly associated with the high initial electrical conductivity (T3 = 25.9 mS/cm) representing substrate salinity, which may have limited nutrient uptake. Despite this, from the third monthly assessment onwards, a gradual recovery in growth was observed in T2 and T3, possibly due to salt leaching and progressive nutrient release. Total and aboveground biomass were significantly higher in T0, while nutrient concentrations showed distinct patterns, with macronutrients exhibiting greater translocation to the shoots, while micronutrients accumulated primarily in the roots, with the exception of Mn, Zn, and B, which were more abundant in the aboveground tissues. Heavy metal levels in soil and plants remained below the limits established by European Directive 86/278/EEC and Italian Legislative Decree No. 99/1992. The second experiment was conducted in Botucatu (São Paulo, Brazil), with the native species Schinus terebinthifolius (Aroeira-pimenteira). The treatments consisted of T0 (commercial control substrate), T1 (4% dewatered and stabilized sewage sludge + 71% urban soil (red latosol) + 25% vermiculite), T2 (8% SS + 67% urban soil + 25% vermiculite) and T3 (12% SS + 63% urban soil + 25% vermiculite), all with six replicates. With monthly monitoring of pH and electrical conductivity (EC) of the leachate, a sharp decrease in salinity was observed over time, with T3 decreasing from 13.1 mS/cm to 5.08 mS/cm. The control treatment (T0) presented higher values of pH, organic matter, potassium, magnesium, sum of bases (SB), base saturation (V%), and boron. In contrast, nutrients such as available phosphorus, calcium, aluminum, sulfur, copper, iron, zinc, and manganese increased proportionally to the sludge dose applied. Regarding seedling development, T0 showed greater growth in the first 30 days, but the sludge treatments outperformed the control at the end of the experiment. There were no significant differences between the sludge treatments in total biomass and chlorophyll content, but all were superior to the control. In the chemical analysis of the plants, N, Ca, and Mn were more abundant in the shoots, while Mg, B, Cu, Fe, and Zn were concentrated in the roots. Phosphorus, potassium, and sulfur were evenly distributed between roots and shoots. Heavy metal levels in the soil remained below the limits established by CONAMA resolution 498/2020. Based on the two experiments, it is concluded that the application of sewage sludge, when monitored for salinity and composition, is viable and safe for use as a substrate in seedling production. Percentages between 12% and 25% proved to be more balanced, combining nutritional benefits without compromising initial plant growth. None of the treatments exceeded the legal limits for heavy metals or presented severe symptoms of toxicity at the end of the experiment. For future studies, we recommend the use of controls with local soil in addition to the commercial substrate, different irrigation depths, and more extensive monitoring of the elements present in the leachate throughout the cycle.

O lodo de esgoto é um resíduo sólido ou semissólido gerado no tratamento de águas residuais, rico em macro e micronutrientes e com potencial para ser utilizado como insumo agrícola ou florestal. Além de fornecer nutrientes, pode melhorar características físicas do solo, como a aeração e a capacidade de retenção de água. No entanto, sua aplicação deve ser feita com cautela, considerando a possível presença de elementos com potencial tóxico que podem prejudicar o desenvolvimento vegetal. Com o objetivo de aprofundar o conhecimento sobre os efeitos da aplicação de lodo de esgoto na produção de mudas, esta tese foi estruturada em duas etapas. A primeira consistiu em uma revisão sistemática da literatura seguida de meta-análise, baseada no protocolo PRISMA 2021, analisando artigos recentes com dados quantitativos sobre os efeitos do lodo de esgoto em solos e plantas. A segunda etapa envolveu dois experimentos em vasos conduzidos por 120 dias em condições de estufa, com diferentes espécies arbóreas utilizadas em arborização urbana, cultivadas sob substratos com proporções variadas de lodo de esgoto doméstico. Os experimentos foram instalados com o objetivo de avaliar os efeitos do lodo de esgoto nos parâmetros químicos do solo, no crescimento vegetal por meio de análises não destrutivas (altura e diâmetro do caule mensais) e nas concentrações de nutrientes acumulados nas plantas, por meio de análises químicas finais em tecidos separados entre parte aérea e raízes. Em ambos experimentos as análises estatísticas incluíram ANOVA e teste de Tukey a 5% de significância, além de análises multivariadas (PCA e PFA) para identificação dos fatores que mais contribuíram para as variações entre os tratamentos. O primeiro experimento foi realizado em Sassari, Sardenha (Itália), utilizando Nerium oleander como espécie. Os tratamentos consistiram em T0 (100% substrato comercial), T1 (25% lodo de esgoto centrifugado (SS) + 50% solo urbano (US) + 25% perlita), T2 (50% SS + 25% US + 25% perlita) e T3 (75% SS + 25% perlita), cada um com seis repetições (vasos). O tratamento controle (T0) apresentou o melhor desempenho inicial em altura, diâmetro do caule e biomassa aérea, seguido por T1, T2 e T3. Nos tratamentos com ≥50% de lodo (T2 e T3), foi observada clorose foliar nas mudas durante os primeiros 60 dias, possivelmente associada à elevada condutividade elétrica inicial (T3 = 25,9 mS/cm) representando salinidade do substrato, o que pode ter limitado a absorção de nutrientes. Apesar disso, a partir da terceira avaliação mensal, observou-se recuperação gradativa no crescimento de T2 e T3, possivelmente devido à lixiviação de sais e liberação progressiva de nutrientes. A biomassa total e aérea foi significativamente maior no T0, enquanto as concentrações de nutrientes mostraram padrões distintos, onde os macronutrientes apresentaram maior translocação para a parte aérea, enquanto os micronutrientes se acumularam majoritariamente nas raízes, com exceção de Mn, Zn e B, que foram mais abundantes nos tecidos aéreos. Os teores de metais pesados no solo e nas plantas permaneceram abaixo dos limites estabelecidos pela Diretiva Europeia 86/278/CEE e pelo Decreto Legislativo Italiano n.º 99/1992. O segundo experimento foi conduzido em Botucatu (São Paulo, Brasil), com a espécie nativa Schinus terebinthifolius (aroeira-pimenteira). Os tratamentos consistiram em T0 (substrato comercial controle), T1 (4% lodo de esgoto desidratado e estabilizado + 71% solo urbano (latossolo vermelho) + 25% vermiculita), T2 (8% SS + 67% solo urbano + 25% vermiculita) e T3 (12% SS + 63% solo urbano + 25% vermiculita), todos com seis repetições. Com o monitoramento mensal do pH e da condutividade elétrica (EC) dos lixiviados, observou-se queda acentuada da salinidade ao longo do tempo, com o T3 passando de 13,1 mS/cm para 5,08 mS/cm. O tratamento controle (T0) apresentou maiores valores de pH, matéria orgânica, potássio, magnésio, soma de bases (SB), saturação por bases (V%) e boro. Em contrapartida, nutrientes como fósforo disponível, cálcio, alumínio, enxofre, cobre, ferro, zinco e manganês aumentaram proporcionalmente à dose de lodo aplicada. Em relação ao desenvolvimento das mudas, o T0 apresentou maior crescimento nos primeiros 30 dias, mas os tratamentos com lodo superaram o controle ao final do experimento. Não houve diferenças significativas entre os tratamentos com lodo quanto à biomassa total e teor de clorofila, mas todos foram superiores ao controle. Na análise química das plantas, N, Ca e Mn foram mais abundantes na parte aérea, enquanto Mg, B, Cu, Fe e Zn se concentraram nas raízes. Fósforo, potássio e enxofre apresentaram distribuição equilibrada entre raízes e parte aérea. Os teores de metais pesados no solo permaneceram abaixo dos limites estabelecidos pela resolução CONAMA 498/2020. Com base nos dois experimentos, conclui-se que a aplicação de lodo de esgoto, quando monitorada quanto à salinidade e composição, é viável e segura para uso como substrato na produção de mudas. Percentuais entre 12% e 25% mostraram-se mais equilibrados, combinando benefícios nutricionais sem comprometer o crescimento inicial das plantas. Nenhum dos tratamentos ultrapassou os limites legais de metais pesados nem apresentou sintomas graves de toxicidade ao final do experimento. Para futuros estudos, recomenda-se o uso de controles com solo local além do substrato comercial, diferentes lâminas de irrigação e monitoramento mais amplo dos elementos presentes nos lixiviados ao longo do ciclo.
Uso de subprodutos como corretivos de solo no setor agrícola e florestal
Keywords: Sewage sludge; biosolids; Urban afforestation; Heavy metals; Plant development